Perceived Overqualification and Intensive Smartphone Use: A Moderated Mediation Model - Peng, Xiongliang; Yu, Kun; Zhang, Kairui; Xue, Hanbing; Peng, Jianfeng (Frontiers in Psychology, 2022)
Previous studies only considered the impact of personal or environmental factors on intensive smartphone use separately, while largely ignoring the impact of person-environment (P-E) fit on it. Drawing upon the P-E fit theory, we propose that perceived overqualification (POQ), an indicator of person-job misfit, positively affects intensive smartphone use via job boredom, and affective commitment moderates this indirect effect. We examined our hypotheses using four-wave time-lag data of 450 workers from 62 teams. The results revealed that POQ raised an individuals’ job boredom and thus increased their intensive smartphone use. In addition, when affective commitment was high, the indirect effect from POQ to intensive smartphone use via job boredom was weaker. The implications, limitations, and future directions of the present research were discussed.